Flood-Irrigated Wheat Cost-Return Budget - O'Brien, Daniel M.; Dumler, Troy J.; Stockton, Roger; Thompson, Curtis R. (My University, 2001)
This publication projects a budget that reflects expected income and costs based on flood-irrigated wheat production.
MF590_2001_10
Keywords: MF590; Economics; Crops; MF